p21Cip1/Waf1 protein and its function based on a subcellular localization [corrected] - Cmielová, Jana; Rezáčová, M (Journal of cellular biochemistry, 2011)
Protein p21(Cip1/Waf1) is a cyclin-dependent kinase inhibitor, which is important in the response of cells to genotoxic stress and a major transcriptional target of p53 protein. Based on the localization, p21(Cip1/Waf1) protein executes various functions in the cell. In the nucleus p21(Cip1/Waf1) binds to and inhibits the activity of cyclin dependent kinases Cdk1 and Cdk2 and blocks the transition from G1 phase into S phase or from G2 phase into mitosis after DNA damage. This enables the repair of damaged DNA. p21(Cip1/Waf1) was also found as an important protein for the induction of replication senescence as well as stress-induced premature senescence. In the cytoplasm, p21(Cip1/Waf1) protein has an anti-apoptotic effect. It is able to bind to and inhibit caspase 3, as well as the apoptotic kinases ASK1 and JNK. The function of p21(Cip1/Waf1) in response to a DNA damage probably depends on the extent of the damage. In the case of low-level DNA damage, the expression of p21(Cip1/Waf1) is increased, it induces cell cycle arrest, and performs also anti-apoptotic activities. However, after extensive DNA damage the amount of p21(Cip1/Waf1) protein is decreased and the cell undergoes apoptosis. Dual function of p21(Cip1/Waf1) was also observed in cancerogenesis. On the one hand, p21(Cip1/Waf1) acts as a tumor suppressor; on the other hand it prevents apoptosis and acts as an oncogene. Better understanding of the role of p21(Cip1/Waf1) in various conditions would help to develop better cancer-treatment strategies.
Keywords: Subcellular Fractions; Cyclin-Dependent Kinase Inhibitor p21; posttranslační úpravy proteinů; Humans; buněčné jádro; Cytoplasm; DNA Damage; lidé; Cell Nucleus; poškození DNA; inhibitor p21 cyklin-dependentní kinasy; cytoplazma; Protein Processing, Post-Translational; subcelulární frakce